AB0374 Nontuberculous mycobacterium infections in patients with rheumatoid arthritis: a single-centre experience in japan. (12th June 2018) - Hayashi, M.; Funamura, K.; Maeda, M.; Kanamono, T.
Abstract : Background: Objectives: Nontuberculous mycobacteria (NTM) infection has been increasing in both general population and immunocompromised patients in Japan. This study aimed to identify the incidence and clinical characteristics of NTM infections in patients with rheumatoid arthritis (RA). Methods: We performed a cross-sectional analysis and assessed 11 RA patients, who were all female, complicated with NTM (mean age, 66.6 years) at our institute. We examined Steinbrocker Stage and Class, disease duration, positivity of anti-CCP antibody and rheumatoid factor, HAQ-DI, DAS28-ESR, NTM species, radiological features, methotrexate use and dosage, prednisolone use and dosage, biological agent use, and anti-NTM therapy. Results: Average values obtained with SD were as follows: age (years), 66.6±8.0; Steinbrocker Stage I, 1; II, 0; III, 1; and IV, 9; Class 1, 2; 2, 5; 3, 4; and 4, 0; disease duration (months), 274.9±126.9; positivity of anti-CCP antibody, 80.0%; positivity of rheumatoid factor, 100%; HAQ-DI, 1.35±0.72; DAS28-ESR, 3.61±0.90; detection by sputum culture, 81.8%; NTM species, M. avium, 8 cases and M. intracellulare, 3 cases; bronchiectasis, 90.9%; interstitial pneumonia, 0%; methotrexate use and dosage (mg/week); 63.6% and 7.4±3.4; prednisolone use and dosage (mg/day); 81.8% and 4.3±2.0; biological agent use, 45.5%; and anti-NTM therapy, 36.4%. Conclusions: At our institute, RA patients complicated with NTM were long-standing, had high disease activities and worse HAQ-DI. In all five patients (45.5%) who were treated with biologics, 3 who had preceding episodes of NTM infection were treated with anti-NTM therapy before treatment with biologics, and the other 2 who had asymptomatic NTM infection after treatment with biologics were not treated with anti-NTM therapy thereafter. In RA patients who are treated with biologics, it is necessary to perform sputum cultures constantly to detect possible NTM infections. This finding is important in the management of RA complicated with NTM. Disclosure of Interest: None declared